Medical Gases: A Novel Strategy for Attenuating Ischemia—Reperfusion Injury in Organ Transplantation? - Arunotai Siriussawakul; Lucinda I. Chen; John D. Lang (Journal of Transplantation)
Ischemia reperfusion injury (IRI) is an inevitable clinical consequence in organ transplantation. It can lead to early graft nonfunction and contribute to acute and chronic graft rejection. Advanced molecular biology has revealed the highly complex nature of this phenomenon and few definitive therapies exist. This paper reviews factors involved in the pathophysiology of IRI and potential ways to attenuate it. In recent years, inhaled nitric oxide, carbon monoxide, and hydrogen sulfide have been increasingly explored as plausible novel medical gases that can attenuate IRI via multiple mechanisms, including microvascular vasorelaxation, reduced inflammation, and mitochondrial modulation. Here, we review recent advances in research utilizing inhaled nitric oxide, carbon monoxide, and hydrogen sulfide in animal and human studies of IRI and postulate on its future applications specific to solid organ transplantation.